Effect of Tax Morale, Tax Sanctions, and Tax Amnesty Policy on Taxpayer Compliance - Kurnia Kurnia; Diza Amalia (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Taxpayer compliance is fulfilling tax obligations voluntarily, where a taxpayer is responsible for setting its own tax obligations accurately and timely pay and report taxes. This study aims to examine and analyze the effect of tax morale, tax sanctions, and tax amnesty policy on taxpayer compliance. The object in this study is a non-employee individual taxpayer registered in the KPP Pratama Makassar Utara 2023 region. This study used a sample of 100 respondents who are non-employee individual taxpayers. Non-probability sampling method using convenience sampling. In this study researchers used the slovin formula. Data analysis technique is done with descriptive statistical analysis and software SPSS-IBM ver 26.0. The results of this study indicate that simultaneously tax morale, Tax sanctions, and tax amnesty policy against Kpeatuhan taxpayers. And partially tax morale, Tax sanctions, and tax amnesty policies have a positive effect on taxpayer compliance at KPP Pratama Makassar Utara 2023 this shows good results.